2020
DOI: 10.1002/pds.5169
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating patient generated health data into pharmacoepidemiological research

Abstract: Epidemiology and pharmacoepidemiology frequently employ Real-World Data (RWD) from healthcare teams to inform research. These data sources usually include signs, symptoms, tests, and treatments, but may lack important information such as the patient's diet or adherence or quality of life. By harnessing digital tools a new fount of evidence, Patient (or Citizen/Person) Generated Health Data (PGHD), is becoming more readily available. This review focusses on the advantages and considerations in using PGHD for ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Additionally, the availability of patient-generated data from home monitoring devices (e.g., pulse oximeters, pacemakers, glucometers), wearables, mobile applications, social media, and other sources is increasing, and incorporating these data sources into case-identifying algorithms, and studies validating their use, will be important in the future. 34…”
Section: Newer Approaches To Enhance the Validity Of Case-identifying...mentioning
confidence: 99%
“…Additionally, the availability of patient-generated data from home monitoring devices (e.g., pulse oximeters, pacemakers, glucometers), wearables, mobile applications, social media, and other sources is increasing, and incorporating these data sources into case-identifying algorithms, and studies validating their use, will be important in the future. 34…”
Section: Newer Approaches To Enhance the Validity Of Case-identifying...mentioning
confidence: 99%
“…Similarly, patient reported information from connected devices might also provide data appropriate as outcomes for adaptive trials in this field. 26 Examples include accelerometer data from smartphones about physical activity, home blood pressure or glucose monitors, especially if delivered via Bluetooth connections that require minimal patient manipulation and can be quickly acquired. Their increasing real time data availability could provide avenues for future adaptive trials.…”
Section: Choice Of Outcomes and Interim Analysesmentioning
confidence: 99%
“…11,12 A variety of initiatives to improve the data landscape are underway, including linking and curating "research-ready" data sets, sometimes including patient-generated health data or patient-reported outcomes. [13][14][15][16][17] These data are already advancing the quality of RWE by reducing missing data and enabling studies to measure patient-centered outcomes. 15 Nevertheless, even these more advanced data sets are prone to missing information and lack context regarding whether or why subjects delay treatment or are nonadherent to care plans or how other life factors, including social determinants of health, affect satisfaction, experiences, and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] These data are already advancing the quality of RWE by reducing missing data and enabling studies to measure patient-centered outcomes. 15 Nevertheless, even these more advanced data sets are prone to missing information and lack context regarding whether or why subjects delay treatment or are nonadherent to care plans or how other life factors, including social determinants of health, affect satisfaction, experiences, and outcomes. 18 Context regarding patient experiences is still needed to explain data trends.…”
Section: Introductionmentioning
confidence: 99%